História de vida professoral de Mário Moacyr Porto: a cultura jurídica em favor dos direitos humanos (1950 – 1969) - Lima, Juliana Augusta Dionisio de (2016)
At teacher life histories, the teachers figure has highlight, being research object for studies about the teacher profession. At this dissertation, the life history of teacher Mário Moacyr Porto is an information source that searches a reflection about the form of teacher professional identify and its educative practices at the form-research perspective. At the performed effort to rebuild this history, was necessary to use the bibliographical gender, differently to the epical narration of historical characters, but establishing a dialogical parallel between the subject and the context that he is placed. In this challenge of finding methodological ways for the historiography, the New Cultural History shows as a movement that bring the cultural aspects as meeting possibility with new objects, sources and methodologies, that let to access new views of History investigation. Starting with the qualitative study of the teacher life trajectory uncovering, in the union between history and memory, by the Oral History was possible to infer about meaning educative aspects at the Paraíba’s Education History. Constitutes objective of the research to analyze the teacher life history of Mário Moacyr Porto, verifying his paper at the Paraíba’s juridical culture build, knowing his active participation in the intellectual militarism, practice that searches the justice establishment, fundamental rights lien, foment and dissemination of democratic ideals. His participation was found in important moments at the educational setting, being involved with the fight of the Law College implantation, the University of Paraíba federalization and the elaboration and teaching of the 1st subject of Civil Law, corroborating to the juridical-educational form of Paraíba.